Construction Business Process Reengineering (CBPR): A Case Study of Construction Organizations in Malaysia - O.W.M. Sabki; M.N. Mohd Nawi; O. Mohamed; F. Azzli (Institut Teknologi Bandung, 2005)
Abstract. Business Process Reengineering (BPR) is currently one of the most popular catchwords. Companies hope to break the